A hypothetical urban layout generation model for exploring land use impacts on travel behavior. (July 2022) - Lyu, Xiaoming; Han, Qi; de Vries, Bauke
Highlights: The ULG model is designed for land use-travel behavior simulation research. The generated urban layouts correspond to the D-variables. A new component in the ULG model is the simulation of population density. The ULG model satisfies the requirements for land use-travel behavior simulation. Exploring how the D-variables affect travel behavior is the core application. Abstract: In urban planning, land-use policies are commonly applied to reduce automobile travel and encourage active transport because land use is believed to affect travel behavior. However, a debate about such effects continues in literature. Empirical studies differing in context, methodology, and geographic scale come to different results. Although questioned because of self-selection, the accumulated empirical evidence provides a solid foundation for conducting simulation research that helps systematically examine the effects of land use attributes on travel behavior. This paper introduces an urban layout generation (ULG) model specially developed for simulations. The ULG model is not a land use and transport interaction model. It generates hypothetical urban layouts corresponding directly to D-variables, a set of land use measurements widely used in empirical studies. The D-variables are controlled on multiple spatial scales in the ULG model. Besides the spatial aspects of the road network and land use commonly included in virtual city models, the ULG model also simulates the population density. Performance tests showed the ability of the ULG model to generate hypothetical though reasonable urban layouts which meet the requirements of simulation research of land use and travel behavior. Finally, several examples combing the ULG model and a travel behavior simulation model show potential applications of the ULG model.